360-Degree Complex Primary Reconstruction Using Porous Tantalum Cages for Adult Degenerative Spinal Deformity. Issue 6 (September 2019) - Butler, Joseph S.; Lui, Darren F.; Malhotra, Karan; Suarez-Huerta, Maria L.; Yu, Haiming; Selvadurai, Susanne; Agu, Obiekezie; Molloy, Sean
Study Design: Retrospective cohort study. Objective: To assess both implant performance and the amount of correction that can be achieved using multilevel anterior lumbar interbody fusion (ALIF). Methods: Retrospective cohort study (n = 178) performed over a 4-year period. Surgical variables examined included blood loss, operative time, perioperative complications, and secondary/revision procedures. Follow-up radiographic assessment was performed to record implant-related problems. Radiographic parameters were examined pre- and postoperatively. Health-related quality of life (HRQOL) outcome measures were collected preoperatively and at 6 weeks, 6 months, 1 year, and 2 years postoperatively. Descriptive and comparative statistical analysis, using paired-sample t test and repeated-measures analysis of variance (rANOVA), was performed. Results: Lumbar lordosis increased from 42° ± 17° preoperatively to 55° ± 11° postoperatively ( P < .001). The visual analog scale back pain mean score improved from 8.3 ± 1.5 preoperatively to 2.6 ± 2.4 at 2 years ( P < .001). The mean Oswestry Disability Index improved from 69.5 ± 21.5 preoperatively to 19.9 ± 15.2 at 2 years ( P < .001). The EQ-5D mean score improved from 0.2 ± 0.2 preoperatively to 0.8 ± 0.1 at 2 years ( P = .02). There were no neurological, vascular, or visceral approach–related injuries reported. No rod breakages and no symptomatic nonunions occurred. There was one revision procedure performed for fracture. Conclusions: The use of porous tantalum cages as part of a 360-degree fusion to treat adult degenerative spinal deformity has been demonstrated to be a safe and effective strategy, leading to good clinical, functional, and radiographic outcomes in the short term.